An integrated physiology, cytology, and proteomics analysis reveals a network of sugarcane protoplast responses to enzymolysis - Zhang, Demei; Wang, Rui; Xiao, Jiming; Zhu, Shuifang; Li, Xinzhu; Han, Shijian; Li, Zhigang; Zhao, Yang; Shohag, M. J. I.; He, Zhenli; Li, Suli (Frontiers in Plant Science, 2022)
The protoplast experimental system eis an effective tool for functional genomics and cell fusion breeding. However, the physiological and molecular mechanisms of protoplast response to enzymolysis are not clear, which has become a major obstacle to protoplast regeneration. Here, we used physiological, cytological, proteomics and gene expression analysis to compare the young leaves of sugarcane and enzymolized protoplasts. After enzymatic digestion, we obtained protoplasts with viability of ＞ 90%. Meanwhile, the content of malondialdehyde, an oxidation product, increased in the protoplasts following enzymolysis, and the activity of antioxidant enzymes, such as peroxidase (POD), catalase (CAT), acid peroxidase (APX), and O2-, significantly decreased. Cytologic analysis results showed that, post enzymolysis, the cell membranes were perforated to different degrees, the nuclear activity was weakened, the nucleolus structure was not obvious, and the microtubules depolymerized and formed several short rod-like structures in protoplasts. In this study, a proteomics approaches was used to identify proteins of protoplasts in response to the enzymatic digestion process. GO, KEGG, and KOG enrichment analyses revealed that the abundant proteins were mainly involved in bioenergetic metabolism, cellular processes, osmotic stress, and redox homeostasis of protoplasts, which allow for protein biosynthesis or degradation. RT-qPCR analysis revealed that the expression of osmotic stress resistance genes, such as DREB, WRKY, MAPK4, and NAC, was upregulated, while that of key regeneration genes, such as CyclinD3, CyclinA, CyclinB, Cdc2, PSK, CESA, and GAUT, was significantly downregulated in the protoplasts. Hierarchical clustering and identification of redox proteins and oxidation products showed that these proteins were involved in dynamic networks in response to oxidative stress after enzymolysis. Our findings can facilitate the development of a standard system to produce regenerated protoplasts using molecular markers and antibody detection of enzymolysis.